Semiconductor nanomaterials for flexible technologies : from photovoltaics and electronics to sensors and energy storage/harvesting devices - Sun, Yugang; Rogers, John A., 1967- (Amsterdam : William Andrew, 2010)
'This book is an overview of the strategies to generate high-quality films of one-dimensional semiconductor nanostructures on flexible substrates (e.g., plastics) and the use of them as building blocks to fabricating flexible devices (including electronics, optoelectronics, sensors, power systems). In addition to engineering aspects, the physics and chemistry behind the fabrication and device operation will also be discussed as well. Internationally recognized scientists from academia, national laboratories, and industries, who are the leading researchers in the emerging areas, are contributing exceptional chapters according to their cutting-edge research results and expertise. This book will be an on-time addition to the literature in nanoscience and engineering. It will be suitable for graduate students and researchers as a useful reference to stimulate their research interest as well as facilitate their research in nanoscience and engineering'--From publisher.
Flexible organic single-crystal field-effect transistors / Alejandro L. Briseno -- Chemically synthesized semiconductor nanowires for high-performance electronics and optoelectronics / Xiangfeng Duan and yu huang -- Fast flexible electronics made from nanomembranes derived from high-quality wafers / Zhenqiang Ma and Guoxuan Qin -- The films of single-walled carbon nanotubes for flexible electronic device applications / Congjun Wang and Qing Cao -- Flexible field emitters based on carbon nanotubes and other materials / Soo-Hwan Jeong and Kun-Hong Lee -- Flexible solar cells made of nanowires/microwires / Jongseung Yoon, Yugang Sun and John A. Rogers -- Zinc oxide nanowire arrays on flexible substrates : wet chemical growth and applications in energy conversion / Sheng Xu, Benjamin Weintraub and Zhong Lin Wang -- Flexible energy storage devices using nanomaterials / Victor L. Pushparj, Sunnalakshmi Sreekala, Omkaram Nalamasu and Pulickel M. Ajayan -- Flexible chemical sensors / H. Hau Wang -- Mechanics of stiff thin films of controlled wavy geometry on compliant substrates for stretchable electronics / Jianliang Xiao, Hanqing Jiang, Yonggang Huang and John A. Rogers.
Includes bibliographical references and index.
Keywords: Semiconductor films; Nanostructured materials; Nanostructures